COVID-19 and helminth infection: Beyond the Th1/Th2 paradigm - Paniz-Mondolfi, Alberto E.; Ramírez, Juan David; Delgado-Noguera, Lourdes A.; Rodriguez-Morales, Alfonso J.; Sordillo, Emilia M. (PLoS neglected tropical diseases, 2021)
[...]in these South American populations, the high prevalence of intestinal parasitosis with soil-transmitted helminths does not appear to have provided a benefit in terms of SARS-CoV-2-related morbidity or mortality. [...]a recent study by Yatsunenko and colleagues [12] has revealed differences in bacterial assemblages and functional gene repertoires between Amerindians in the Venezuelan Amazon when compared to US residents. [...]it is essential to remember the manifold negative effects of intestinal parasitosis.